0085 Injury reporting, employer lodgement and compensation payment delays and duration of wage replacement in injured workers. (21st August 2017) - Cocker, Fiona; Smith, Peter; Kelsall, Helen; Sim, Malcolm
Abstract : Objective: To determine if delays in the workers' compensation process, indicated by failures in claim filing, adjudication and provision of wage replacement (WR), are associated with poorer RTW outcomes. Methods: This study examined standard workers' compensation claims with an injury date between January 2007 and December 2012, with at least one-day of WR, and which were not terminated for reasons other than RTW within the first 12 months of the claim (n=80, 322). Logistic regression models explored the association between: i) delays in the injured workers (IWs) claim lodgement, the IWs employer's lodgement of the claim with the insurer, and receipt of first compensation payment, and accumulating 52 weeks of WR; and ii) socio-demographic/economic, occupational, and injury-related factors and the aforementioned delays. Results: All delays were associated with increased odds of reaching 52 weeks of WR. The more delays, the greater odds of a long-term claim. Different factors were associated with each different delay. Conclusions: The predictive ability of delays in claim lodgement and processing and receipt of compensation payments demonstrate where improved claims management and adjudication could reduce the proportion of workers on long term WR.